2021
DOI: 10.29228/jrp.88
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the usage of herbal products during the Covid-19 pandemic

Abstract: During the COVID-19 pandemic period, herbal products have been used by patients for many purposes. In this study, the frequency of use of herbal products during the COVID-19 pandemic was investigated. This research is a cross-sectional study. Patients who admitted to an academic hospital (Gazi University Faculty of Medicine) Chest Diseases Clinic between November 2020-January 2021 were included in the study. It was concluded that approximately 32% of the patients used herbal products during the pandemic period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In Bulut et al , the most frequently used herbal supplements were turmeric (20.4%), ginger (12.2%), green tea (4.1%), and echinacea (4.1%) [24] , compared to lemon (54.68%), garlic (46.76%), ginger (46.04%), thyme (43.88%), and linden (37.41%) in our study. Similarly, many of the patients in our study who had experienced COVID-19 infection used lemon (64.77%), ginger (57.95%), thyme (47.73%), linden (47.73%), and garlic (32.95%) supplements.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…In Bulut et al , the most frequently used herbal supplements were turmeric (20.4%), ginger (12.2%), green tea (4.1%), and echinacea (4.1%) [24] , compared to lemon (54.68%), garlic (46.76%), ginger (46.04%), thyme (43.88%), and linden (37.41%) in our study. Similarly, many of the patients in our study who had experienced COVID-19 infection used lemon (64.77%), ginger (57.95%), thyme (47.73%), linden (47.73%), and garlic (32.95%) supplements.…”
Section: Discussionsupporting
confidence: 44%
“…A cross-sectional study found that 62.8% of participants, who were recruited from three different countries, used DSs including herbal preparations, vitamins, and minerals during the first 3 months of the COVID-19 pandemic [23] . In another study, approximately 32% of patients who presented to a chest diseases clinic during the pandemic used herbal DSs [24] . Approximately half of our patients (50.18%) used DSs; the high rates of DS use during the pandemic could be explained by the limited treatment options available for COVID-19, people's desire to strengthen their immune systems, and the high availability of DSs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations